Toll-like receptors in atherosclerosis. - Falck-Hansen, M; Kassiteridi, C; Monaco, C (2013)
Atherosclerosis, the leading cause of cardiovascular disease (CVD), is driven by inflammation. Increasing evidence suggests that toll-like receptors (TLRs) are key orchestrators of the atherosclerotic disease process. Interestingly, a distinct picture is being revealed for individual receptors in atherosclerosis. TLRs exhibit a complex nature enabling the detection of multiple motifs named danger-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs). Activation of these receptors triggers an intracellular signalling cascade mediated through MyD88 or TRIF, leading to the production of pro- and anti-inflammatory cytokines. In this review we explore key novel findings pertaining to TLR signalling in atherosclerosis, including recently described endosomal TLRs and future directions in TLR research.